A teosinte-derived allele of ZmSC improves salt tolerance in maize - Li, Xiaofeng; Ma, Qiangqiang; Wang, Xingyu; Zhong, Yunfeng; Zhang, Yibo; Zhang, Ping; Du, Yiyang; Luo, Hanyu; Chen, Yu; Li, Xiangyuan; Li, Yingzheng; He, Ruyu; et al. (Frontiers in Plant Science, 2024)
Maize, a salt-sensitive crop, frequently suffers severe yield losses due to soil salinization. In the present study, an introgression line (IL76) was developed through introgressive hybridization between maize wild relatives Zea perennis, Tripsacum dactyloides, and inbred Zheng58 utilizing the tri-species hybrid MTP as a genetic bridge. Genetic variation analysis identified a polymorphic marker on Zm00001eb244520 (designated as ZmSC), which encodes a vesicle-sorting protein, described as a salt-tolerant protein in the NCBI database. Furthermore, gene cloning analysis revealed a non-synonymous mutation at the 1847th base of ZmSC IL76 , where a guanine-to-cytosine substitution occurred resulting in mutation of serine to threonine at the 119th amino acid sequence (using ZmSC Z58 as the reference sequence).Moreover, homologous cloning demonstrated that the variation site derived from Z.Perennis. Transgenic Arabidopsis lines overexpressing ZmSC Z58 exhibited significant reduction in leaf number, root length, and pod number, and the genes in SOS and CDPK pathways were suppressed. Meanwhile, fission yeast strains expressing ZmSC Z58 showed inhibited growth. However, the ZmSC IL76 allele derived from Z. perennis alleviated these negative effects in both Arabidopsis and yeast. The lines overexpressing ZmSC IL76 exhibited significantly higher abscisic acid (ABA) content compared to those overexpressing ZmSC Z58 . Consequently, ZmSC may be involved in regulating the content of ABA and subsequently suppress the expression of downstream genes associated with Ca 2+ signaling in the CDPK and SOS pathways, ultimately exerting a negative effect on salt tolerance. Collectively, our results reveal that ZmSC negatively regulates the salt tolerance in maize by inhibiting downstream gene expression, while the alleles ZmSC IL76 from Z. perennis can alleviate this negative regulatory effect. These findings provide valuable insights and genetic resources for future maize salt tolerance breeding programs.